Detection of hydrocarbon microseepage-induced anomalies by spectral enhancements of Landsat 7 ETM+ images in part of Assam–Arakan Fold Belt, India - Santosh Garain; Debashis Mitra; Pranab Das (Journal of Petroleum Exploration and Production Technology, 2019)
Abstract Subsurface hydrocarbon traps are not correctly sealed, and hydrocarbons move vertically from the reservoir as invisible traces in the form of microseepages. Long-term hydrocarbon microseepages cause surface or near-surface alterations such as bleaching of red beds, enrichment of ferrous iron minerals and higher concentrations of clay and carbonate minerals in soils/rocks. Multi- and hyperspectral remote sensing data have successfully been used to detect such alterations in many parts of the world. In India, such studies have not been carried out till now. In this study, Landsat 7 ETM+ images have been used to find out hydrocarbon microseepage-bearing areas in part of Assam–Arakan Fold Belt in the northeastern part of India. Based on the spectral characteristics of the hydrocarbon microseepage-induced altered minerals, two spectral enhancement techniques, viz. principal component analysis (PCA) and band ratio analysis, have been carried out on the Landsat 7 ETM+ images. PCA reveals that three principal component images—1457PC3, 1345PC2 and 3457PC4—show relatively better enhancement for the hydrocarbon-bearing alteration areas. Again, band ratio analysis of the images indicates that ratio images—3/1, (2 + 5)/(3 + 4) and 7/5—show excellent spectral enhancement for the hydrocarbon-induced mineral alterations. The three PC images have been combined with the three band ratio images to find out probable hydrocarbon microseepage areas. The remote sensing-derived prospect areas have been validated with surface geochemical, seismic/geologic and gravity data available in the area.